2022
DOI: 10.1038/s41598-022-20207-6
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-based ecological momentary assessment reveals mental health benefits of birdlife

Abstract: The mental health benefits of everyday encounters with birdlife for mental health are poorly understood. Previous studies have typically relied on retrospective questionnaires or artificial set-ups with little ecological validity. In the present study, we used the Urban Mind smartphone application to examine the impact of seeing or hearing birds on self-reported mental wellbeing in real-life contexts. A sample of 1292 participants completed a total of 26,856 ecological momentary assessments between April 2018 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…In natural areas where people go to purposely escape the sounds of cities, any anthropogenic noise may be poorly tolerated (Buxton et al, 2021; Uebel et al, 2022). Conversely, detection of bird‐song in people's everyday lives has positive mental health impacts even in the absence of greenspace (Hammoud et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In natural areas where people go to purposely escape the sounds of cities, any anthropogenic noise may be poorly tolerated (Buxton et al, 2021; Uebel et al, 2022). Conversely, detection of bird‐song in people's everyday lives has positive mental health impacts even in the absence of greenspace (Hammoud et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The subjective assessment of those sounds by humans varies with factors such as age and culture, along with the context in which the sound is experienced (Davies, 2013; Van Kempen et al, 2014; Zhang & Kang, 2007). However, even in cities people generally prefer natural over anthropogenic sounds, and exposure to natural sound has been associated with physical and mental health benefits (Buxton et al, 2021; Franco et al, 2017; Hammoud et al, 2022; Yang & Kang, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…and less on external environmental factors such as exposure (or lack of exposure) to nature. Research collaborations between public health professionals and environmental designers, however, are increasingly highlighting the role that external environmental factors including wildlife [50], street trees [51], and public parks [52] play in mental health, creating a much-needed dialogue between the fields of ecology, design, and public health. Improvements in personal health and well-being will not come from lectures, social media posts, or scientific articles alone, but from ongoing direct participation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite growing recognition of the risks of disease transmission (Lawson et al 2018), and the possible negative impacts on biodiversity (Shutt and Lees 2021), the practice of feeding garden birds is clearly a popular and accessible means of connecting with nature in urban environments. Hammoud et al 2022) and restoration (Ratcliffe et al 2013(Ratcliffe et al , 2020Zhu et al 2020). Effects are greater in conditions of perceived species diversity (Cameron et al 2020;Cox and Gaston 2015), and when people actively encounter birds (Cox et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Effects are greater in conditions of perceived species diversity (Cameron et al 2020;Cox and Gaston 2015), and when people actively encounter birds (Cox et al 2018). Hammoud et al (2022) used real-time sampling via a smartphone app and found that reported mental wellbeing was greater when participants could see or hear birds, compared with not seeing or hearing birds. The effects on wellbeing were lasting, independent of the effect of seeing trees, plants or water, and were observed in people with depression as well as those without a mental health condition.…”
Section: Introductionmentioning
confidence: 99%